Aspergillus Oryzae: Multifunctional Powerhouse Revolutionizing Food Industries and Gut Health - Saksham Gupta; Kanchi Khandelwal (International Journal of Fungi, 2025)
Aspergillus oryzae, commonly known as “Koji mold,” is a filamentous fungus extensively utilized in various food industries due to its robust enzymatic activity and generally recognized as safe (GRAS) status. This review explores its diverse applications, focusing on its role in fermented food production, enzyme generation, and contributions to gut health. In the production of fermented foods, such as soy sauce, miso, and sake, A. oryzae serves as a crucial microorganism, breaking down complex carbohydrates and proteins into simple sugars and amino acids, and enhancing flavor and nutritional profiles. Its ability to produce industrial enzymes, including amylases, proteases, and lipases, has made it indispensable in brewing, baking, and the dairy industry. Additionally, A. oryzae-derived enzymes are widely used in developing food thickeners and flavor enhancers, underscoring their biotechnological significance. Emerging studies highlight the potential of A. oryzae in promoting gut health. Fermented foods made with Aspergillus oryzae can support better digestion, balance the gut microbiome, and boost the absorption of nutrients. Its enzymes aid in breaking down complex dietary components, reducing gut inflammation, and supporting overall gastrointestinal well-being. This review consolidates recent advancements in the food industry and explores the symbiotic relationship between A. oryzae and gut health, emphasizing its importance in functional food development.
Keywords: Aspergillus oryzae; Microbes; fermented food; gut health; symbiosis